Ozoniotherapy in the treatment of wounds and diseases in veterinary medicine: literature review (Research, Society and Development, 2022)
Ozone's principles are to increase tissue oxygenation and, consequently, it has been studied in a deeper and more scientific way, in order to propose new protocols for complementary treatments in the most diverse diseases. At present, it has shown a positive action in acute and chronic infectious diseases caused by viruses, bacteria and fungi, in burns, ulcers, among others. Ozone therapy is increasingly studied and applied in order to assist in the various treatments of diseases in veterinary medicine. The main objective of this work was to describe the use of ozone in Veterinary Medicine, its therapeutic indication, mechanism of action, application methods, side effects and contraindications. For this, it was used as a literature review methodology, involving an extensive verification of scientific articles, aiming to describe the new discoveries in the ways of using ozone therapy. It is concluded that more detailed studies are still needed to discuss this form of therapy, thus clarifying the methodologies of its formation and proving more benefits. However, it was observed that it is a great alternative in veterinary medicine for wound healing and treatment of various diseases.